In-tube collision-induced dissociation for selected ion flow-drift tube mass spectrometry, SIFDT-MS: a case study of NO(+) reactions with isomeric monoterpenes - Spesyvyi, Anatolii; Sovová, Kristýna; Španěl, Patrik (Rapid communications in mass spectrometry, 2016)
RATIONALE: Soft chemical ionisation techniques including selected ion flow tube mass spectrometry, SIFT-MS, and proton transfer reaction mass spectrometry, PTR-MS, cannot currently quantify individual isomers present simultaneously in samples, a notable example being atmospheric monoterpenes. A possible solution lies in integrating in-tube collision-induced dissociation, CID, into a selected ion flow-drift tube mass spectrometry, SIFDT-MS, instrument. METHODS: In-tube CID was implemented by applying electrostatic potential difference between the resistive glass flow-drift tube downstream end and the nose cone of a quadrupole mass spectrometer. The resulting inhomogeneous electric field accelerates the product ions along the last 1 mm before the nose cone and causes their dissociation in collisions with molecules of the buffer gas (4% air, 96% helium, 2 mbar). Mass spectra of the product ions of NO(+) reactions with 3-carene, β-pinene, (S)-limonene and their mixture were obtained for variable potential difference. RESULTS: Potential difference up to 47.7 V resulted in dramatic changes in the mass spectra due to fragmentation of the monoterpene radical molecular cations. The main observed fragments correspond to logical losses from different isomeric structures. Fragmentation increases with the potential difference and can be interpreted as single collision dissociation on air molecules at centre-of-mass energies of several eV. Combination of fragmentation patterns at different CID enables distinction of isomers in the mixture on the basis of pseudoinversion. CONCLUSIONS: In-tube CID represents a simple and low-cost extension to SIFDT-MS that allows real-time identification of isomeric products of ion-molecule reactions on the basis of their structural differences and corresponding changes in fragmentation patterns with CID energy without significantly changing the net reaction time important for absolute quantification. Copyright © 2016 John Wiley & Sons, Ltd.